Chemical analysis and organoleptic properties of banana blossoms (Musa paradisiaca) as filler for catfish (Clarias sp.) fish floss. Issue 1 (April 2021) - Perdana, W W; Widowaty, W; Sofia, D R; Setiawan, Y; Hadayanti, D; Zakaria, A
Abstract: Meat floss or known as Abon (Indonesian) made from dried meat and has a fluffy texture similar to cotton coarse. The crude protein content of meat floss was less than 15%. Catfish ( Clarias sp. ) has rough fiber and does not contain many bones that are ideal for the main ingredients for meat floss. Catfish ( Clarias sp. ) cultivated from freshwater can be used as main ingredients for meat floss. To raise the economic value of meat floss, some use banana blossoms ( Musa paradisiaca ) as a filler. This study aims to determine the effect of banana blossoms as a filler and frying temperature on the chemical quality and organoleptic properties of catfish meat floss. The Method of this research is to make catfish meat floss with various banana blossoms and various frying temperatures. The method used is the analysis of variance or the factorial pattern of analysis of variance (ANOVA). The result showed the most preferred sample was the treatment sample with 60% banana blossoms filling and a frying temperature of 170 °C. The samples have the moisture content of 6, 8%, the protein content of 14, 91%, and fat content of 9, 73%, as well as the preferred parameters of color, fragrant, flavor, and texture. The results showed that the use of banana blossoms as a filler in catfish floss improved the quality of shredded and has the potential to be used as a form of food product diversification.